Effective persistence layer synchronous replication heterogonous database - UMP, FSKKP (Faculty of Computer Systems and Software, 2013)
BACKGROUND - Database System is a collection of information. It moves from centralization towards decentralization. - Distributed Database System (DDS) is a collection of multiple independent databases. - Data replication in DDS technology involves copying data between data stores and guarantees data across multiple sites in a distributed environment - Usually replication process depends on the main server. Introducing the up-gradation of the replication process usually pause the system for a routine of time. Fail or crashes of the main server, usually make the entire system stop working (for database driven system)